In vivo evidence of the prevents DSS-induced colitis of Lactiplantibacillus plantarum L15 - Wang, Zengbo; Yang, Liu; Tang, Hongwei; Zhang, Kangyong; Chen, Qingxue; Liu, Caihua; Guo, Yanan; Li, Minghao; Guo, Zengwang; Li, Bailiang (Frontiers in Microbiology, 2022)
Ulcerative colitis (UC) is challenging to treat and severely impacts patients and families. A previous study reported immunomodulatory and anti-inflammatory properties for the Lactiplantibacillus plantarum L15. This study aimed to analyze the preventive properties and mechanistic actions in an in vivo colitis model. The histopathological alteration, inflammation cytokines, and intestinal barri-er function were analyzed. Subsequently, the cecal gut microbiota contents and products from dif-ferent groups were detected. Finally, gene expressions related to the NF-κB signaling process were evaluated. L. plantarum L15 significantly decreased disease activity index, myeloperoxidase activi-ty, pro-inflammatory cytokine (TNF-α, IL-1β, and IL-6) level, and increased weight change, colon length, and production of inflammation-suppressing cytokines. Furthermore, this strain supplemen-tation substantially increased ZO-1, Occludin, and Claudin-1, and MUC2 mRNA expression levels with a corresponding decrease in serum lipopolysaccharide and D-lactic acid contents. Furthermore, L. plantarum L15 improved gut microbiota composition and increased short-chain fatty acid (SCFAs) in the colon content, which significantly reduced the transfer of NF-κB p65 to the nucleus. Our find-ings provide a theoretical basis for L. plantarum L15 as a preventive candidate for UC.